Beginning ASP.NET 4 in VB 2010 - MacDonald, Matthew; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2010)
The most up-to-date and comprehensive introductory ASP.NET book you’ll find on any shelf, Beginning ASP.NET 4 in VB 2010 guides you through Microsoft’s latest technology for building dynamic web sites. This book will enable you to build dynamic web pages on the fly, and assumes only the most basic knowledge of Visual Basic. The book provides exhaustive coverage of ASP.NET, guiding you from your first steps right up to the most advanced techniques, such as querying databases from within a web page and tuning your site for optimal performance. Within these pages, you’ll find tips for best practices and comprehensive discussions of key database and XML principles you need to know in order to be effective with ASP.NET. The book also emphasizes the invaluable coding techniques of object orientation and code-behind, which will start you off on the track to building real-world web sites right from the beginning—rather than just faking it with simplified coding practices. By the time you’ve finished the book, you will have mastered the core techniques and have all the knowledge you need to begin work as a professional ASP.NET developer.
Introducing .NET -- The .NET Framework -- The Visual Basic Language -- Types, Objects, and Namespaces -- Developing ASP .NET Applications -- Visual Studio -- Web Form Fundamentals -- Web Controls -- Error Handling, Logging, and Tracing -- State Management -- Building Better Web Forms -- Validation -- Rich Controls -- User Controls and Graphics -- Styles, Themes, and Master Pages -- Website Navigation -- Working with Data -- ADO.NET Fundamentals -- Data Binding -- The Data Controls -- Files and Streams -- XML -- Website Security -- Security Fundamentals -- Membership -- Profiles -- Advanved ASP.NET -- Component-Based Programming -- Caching -- LINQ and the Entity Framework -- ASP.NET AJAX -- Deploying ASP.NET Applications.
Keywords: Microsoft software; Microsoft .NET Framework; Software engineering; Microsoft and .NET.; Software Engineering/Programming and Operating Systems